Painful skin ulcers in psoriasis patients after taking methotrexate-containing traditional Chinese medicine: a retrospective case series - Zheng, Yunhong; Dubai, Yinzi; Wang, Ruizhe; Luo, Suju (Frontiers in Allergy, 2025)
BackgroundTraditional Chinese Medicine (TCM) has demonstrated certain efficacy in the treatment of psoriasis, a chronic papulosquamous skin disease. However, in rare instances, the use of TCM may exacerbate cutaneous lesions. This study aims to explore whether the methotrexate (MTX) component in TCM may increase the risk of cutaneous ulceration in patients with psoriasis. MTX is also an immunosuppressive agent widely used in the treatment of various dermatologic conditions.MethodsWe retrospectively analyzed the medical records of five patients who developed painful skin ulcers at primary psoriatic sites after taking TCM. Evaluated indicators included hemocytopenia, liver function, serum MTX concentration, and ABCB1 gene polymorphisms. Histopathological examination was also performed on ulcerative tissue samples.ResultsAmong the five patients, two developed hemocytopenia and two had abnormal liver function. Serum MTX concentrations in two patients ranged from 0.03 to 0.11 μmol/L (<0.1 μmol/L at 72 h after MTX administration). The ABCB1 genotypes AA and AG were detected in two different patients. Histopathological findings revealed dyskeratosis of keratinocytes, dermal vasodilation, and inflammatory cell infiltration. Rescue treatment with oral folic acid was administered to three patients, leading to complete healing of all lesions within two weeks. The remaining two patients showed gradual improvement in skin ulcers after discontinuing TCM.ConclusionsTCM containing MTX may induce skin ulceration in rare cases among patients with psoriasis.